The clinical impact of expert pathological review on lymphoma management: a regional experience. - Lester, J; Dojcinov, S; Attanoos, R; O'Brien, C; Maughan, T; Toy, E; Poynton, C (2003)
The All Wales Lymphoma Panel (AWLP) was established in January 1998 to provide a central expert pathological review service for district general hospital pathologists. A discordance rate of 20% between the submitted and reviewed diagnosis has previously been identified. It has not been known whether this change in diagnosis affects clinical management. Ninety-nine patients whose diagnosis was changed as a result of central pathological review are presented. Between January 1998 and August 2000, 125 of 745 (17%) specimens submitted for AWLP review had a consequent change in pathological diagnosis. Of these 125 specimens, 99 (79%) complete case notes were recovered. In all 99 cases, a hypothetical management plan was generated using collected data, clinical protocols and the submitted pathological diagnosis. These plans were compared with the actual management patients received based on the reviewed diagnosis proffered by the AWLP. Forty-six of 99 (46%) cases had a change in management as a result of central pathological review. Overall, management was changed in 8% of cases referred for central pathological review. In conclusion, expert central pathological review has a direct effect on patient management.